Canadian financial stress and macroeconomic conditions - Thibaut Duprey (Bank of Canada, 2020)
I construct a new composite measure of systemic financial market stress for Canada. Compared with existing measures, it better captures the 1990 housing market correction and more accurately reflects the absence of diversification opportunities during systemic events. The index can be used for monitoring. For instance, it reached a peak during the COVID-19 pandemic second only to the 2008 global financial crisis. The index can also be used to introduce non-linear macrofinancial dynamics in empirical macroeconomic models of the Canadian economy. Macroeconomic conditions are shown to deteriorate significantly when the Canadian financial stress index is above its 90th percentile.
Keywords: C32; G01; E44; 330; Central bank research; Financial markets; Financial stability; Monetary and financial indicators